2015
DOI: 10.1590/1984-70332015v15n1a4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of cotton landraces found in the Paraíba and Rio Grande do Norte states

Abstract: -The objective of this study was to estimate genetic diversity of cotton mocó planted in Paraíba and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…latifolium Hutch.) produces one of the most important textile fiber of the world, and offers various utility products with great relevance in the Brazilian and the world's economy (Carvalho et al 2015a, Menezes et al 2015, Morello et al 2015. However, changes in spinning technology, competition with synthetic fibers, and the globalization of cotton production and textile products increase the demand for higher quality fiber, making the length of fiber one of the main traits to be improved (Smith et al 2008, Carvalho et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…latifolium Hutch.) produces one of the most important textile fiber of the world, and offers various utility products with great relevance in the Brazilian and the world's economy (Carvalho et al 2015a, Menezes et al 2015, Morello et al 2015. However, changes in spinning technology, competition with synthetic fibers, and the globalization of cotton production and textile products increase the demand for higher quality fiber, making the length of fiber one of the main traits to be improved (Smith et al 2008, Carvalho et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…PIC values vary among genotypes, and higher values indicate greater genetic diversity and allelic differentiation. Menezes et al (2015) reported that markers with higher PIC values are more effective in identifying polymorphism within a specific population. In a study conducted by Cai et al (2014) In context to ISSR, PIC values varied from 0.518 to 0.043, with an average value of 0.25 (Table 3).…”
Section: Structure Analysis Using Issr and Est-ssr Markersmentioning
confidence: 99%
“…This plant has a high level of genetic diversity in this region (Menezes et al, 2017). In years of intense droughts, after the harvesting of feathers, the use of plant leaves in the diets contributes to the nutritional supplementation to feed cattle (Menezes et al, 2015(Menezes et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%